Effects of Foliar Application of Proline, Yeast Extract and Urea on Growth and Yield of Hyssop (Hyssopus officinalis L.) under Intercropping with Fenugreek (Trigonellafoenum graecum L.) - Abolghasem Gharakhani-Beni; Hamidreza Javanmard; Abdollah Ghasemi Pirbalouti; Ali Soleymani; Ahmadreza Golparvar (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
In this experiment the effect of the foliar applications of proline, yeast extract, and urea on thegrowth, yield, and quality characteristics of active substance of hyssop was investigated. This study was done in a split plot experimentalin randomized complete block design with three replications at the experimental field of Shahrekord University in 2017. The main plot was sole cropping of fenugreek, sole cropping of hyssop, and three intercropping ratios i.e. %50 fenugreek + %50 hyssop, %25 fenugreek + %75 hyssop, and %75fenugreek + %25 hyssop. The sub-plot was four levels foliar sprayings i.e. non-spraying or control and foliar sprayings of proline, yeast, and urea.The results showed that the intercropping and foliar sprayings of proline, yeast, and urea were significantly affected on some characteristics of hyssop such as plant height, number of lateral branches and the contents of chlorophyll a and b. The amount of land equivalent ratio (LER) in the intercropping was more than hyssop monoculture. In addition, LER under the foliar spraying of proline, yeast, and ureawas higher in comparison with non-foliar application.The pattern planting and foliar sprayings of proline, yeast, and urea had significant impacts on the proline content in the hyssop plants. Also, effect of monoculture of hyssop on essential oil content and yield of hyssop wassignificant; however, the foliar application of proline, yeast, and ureahad not influences on two these characteristics. In conclusion, the intercropping hyssop with legume (fenugreek) and the foliar sprayingsof proline, yeast, and urea can improve somegrowth parameters and active substance or the quantity and quality essential oilof hyssop.